Atenuação de ruído de impacto em pisos de edificações de pavimentos múltiplos - Rafaela Ferraz (2008)
In Brazil as well in many countries, the development of constructive systems to provide acoustic comfort in buildings has been a permanent concerning nowadays in order to improve the life quality of its users. The annoyance caused by impact noise in multistory buildings generated by object fall and footfall can be controlled within the floor project and detailing. In this research, some concepts of building acoustic and its noise control systems are studied to support the floor project in buildings. Within this context, the standard and criterion were research and collected in order to classify comfort conditions which gave the basis for the realization of experimental studies of impact noise in multi-story buildings floors. Thus, 16 tests were performed in accordance withISO 140-7:1998, as case studies, for the determination of the acoustic properties of noise impact isolation in floating floor systems. The analysis and interpretation of experimental results showed that every studied floating floor systems, with resilient materials tested in accordance with ISO 140-7:1998, complies with the reference valuesrecommended by the FHA. Were also realized case studies using simplified tests proceedings in 32 reduced floating floor systems. Comparison of performance results between the simplified testes and those realized in compliance with ISO 140-7:1998, identifies various aspects related to the equivalence between these tests, both global andspectral aspects. Verify that the global values was found in simplified tests were similar to those of floating floors made in accordance with ISO 140-7:1998, and spectral values showed many differences. This work was also made comparisons between the criteria of impact insulation of floors established by the Brazilians standards and those recommended by FHA (USA), in the light of results from tests of floating floors. It wasfound that the criteria established by ABNT NBR 15575-3: 2008 are much less restrictive than the criteria recommended by the FHA. It is also, that the criteria of NBR 15575-3: 2008 are demanding performance of the impact of noise insulation of floors well below the constructive systems currently practiced in the country.